Innovative Teaching Methods to Reduce the Achievement Gap in Inner-City Schools - Hasriathy Hasriathy (Generasi Sains Indonesia, 2024)
This examine explores innovative teaching methods geared toward lowering the achievement gap in internal-city schools. Utilizing a qualitative studies method, statistics were accrued through semi-structured interviews and recognition groups with educators, administrators, and college students from numerous urban faculties. The findings spotlight the capability of technology integration, customized learning, culturally responsive coaching, social-emotional studying, project-based studying, and mixed learning in creating inclusive and effective academic environments. The observe also emphasizes the critical function of community and family engagement. While those strategies display promise, their a hit implementation calls for addressing challenges associated with funding, instructor education, and equitable access to resources. This studies contributes to the continuing efforts to shut the success hole and make certain educational fairness for all college students.